Viral diseases of reptiles. Issue 6 (9th June 2016) - Marschang, Rachel E.
Abstract : As reptile medicine has grown and more is known about various diseases in these animals, the importance of some viruses in clinical reptile practice has become more widely understood. More and more studies have become available on the prevalence of infections with specific viruses in different reptiles, as well as clinical signs associated with these infections. An increasing body of knowledge on the genomes of specific viruses is available, which has also led to the development of more sensitive and more specific testing methods. The availability of new, high‐throughput sequencing methods has allowed the detection of previously unknown viruses that are associated with specific disease syndromes in the tissues of reptiles. All of this has led to a much expanded pallet of diagnostic tests available to practitioners, while knowledge of the interpretation of results may, in many cases, have lagged behind. This article describes some important viruses in reptiles that may be commonly seen in private practice, and how to diagnose them.